Dos discursos católico, espírita e evangélico pentecostal: competência discursiva e simulacros das práticas de fé - Gonçalves, Iverton Gessé Ribeiro (2020)
This research, entitled Dos discursos católico, espírita e evangélico pentecostal: competência discursiva e simulacros das práticas de fé, develops an investigative path that delimits itself in analyzing the practices of catholic, spiritist and pentecostal evangelical faiths, of the semantic constrains system that regulate the discursive practices of each religion, with the purpose of apprehending a model of discursive competence and the simulacra produced by each of these discourses. This study justifies itself by the necessity of investigating, in the discursive practices of faith, the coercion exercised upon the people in their practice of faith, with emphasis in the semantic features given by the model of discursive competence, in order to apprehend, from the people, a discursive behavior that serves as an example of faith incorporated in the discourse and its relation with the interdiscourse. The objective of this study is to analyze the discursive practices of these three religious strands (catholic, spiritist and pentecostal evangelical), seeking to understand the semantic constrains that each system imposes and the construction of a discursive competence model taken as an example of faith. The conceptions of cultural system, religion, symbolic representation and myth, developed inside the Anthropology of Religion by Bourdieu (1974, 1989), Cassirer (1992), Eliade (1979, 1992, 1998) and Geertz (2008), compose the first part of the theoretical path that supports this study. The theoretical interface completes itself with the study of the global semantic, the discursive competence, the scenography and the discursive ethos, developed by Maingueneau (1997, 2000, 2008a, 2008b, 2008c, 2010). The corpora of this research is composed by the indoctrinate literature of each religious segment, represented by the Catechism of the Catholic Church (1997), What is Spiritism (2009) and Declaration of faith (2016). Beyond this material, the corpora complement itself with semi-structured questionnaire applied to people from each of the religious strands. The research classifies itself as exploratory-descriptive; bibliographic; documentary and field research with a qualitative approach. Each religious discourse inserts itself in the interdiscourse fostering its identity from the constitutive relations that they establish with each other. Therefore, the faith behaviors inside each religious configuration raise a discursive competence that lives the constant necessity of legitimizing itself, either through denial and the silencing of the Other, or through the cosmogonic discursivization of its source with the transcendent.